Micro-Grippers with Femtosecond-Laser Machined In-Plane Agonist-Antagonist SMA Actuators Integrated on Wafer-Level by Galvanic Riveting - Mayra Garcés-Schröder; Lars Hecht; Anke Vierheller; Monika Leester-Schädel; Markus Böl; Andreas Dietzel (Proceedings, 2017)
In-plane shape memory alloy (SMA) actuators operated in agonist-antagonist mode are integrated on silicon micro-grippers. The actuator elements are cut out of sheet material in a femtosecond laser ablation process. The assembly process is carried out on wafer-level, and the fixation realized by galvanic riveting. The initial deformation of the differential actuators needed to access their actuation potential is implemented during the gripper connection to energy supply.